Treatment of Popliteal (Baker) Cysts With Ultrasound-Guided Aspiration, Fenestration, and Injection: Long-term Follow-up. (September 2015) - Smith, Marvin K.; Lesniak, Bryson; Baraga, Michael G.; Kaplan, Lee; Jose, Jean
Background: The purpose of this study was to determine the efficacy of ultrasound-guided aspiration, fenestration, and injection as a treatment in patients with symptomatic popliteal cysts. Hypothesis: Ultrasound-guided aspiration, fenestration, and injection (UGAFI) is an effective and safe treatment option for symptomatic popliteal cysts. Study Design: Retrospective cohort study. Level of Evidence: Level 3. Methods: Patients who received a UGAFI of popliteal cysts from 2008 to 2011 were identified. Preaspiration (PA) and follow-up Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, cyst recurrence, complications, cyst complexity, and size were obtained and compared for statistical significance. UGAFI involved aspiration of fluid through a spinal needle, fenestration of the cyst walls and septations, and injection of 1 mL (40 mg) triamcinolone (Kenalog) and 2 mL 0.5% bupivacaine (Sensorcaine) into the decompressed remnant. Results: The mean PA WOMAC score (48.55) improved significantly at final follow-up (FFU) to 17.15 ( P < 0.0001) for 47 patients. Within the WOMAC subcategories, there was also a significant difference in pain (PA, 10.68; FFU, 3.94; P < 0.0001), stiffness (PA, 4.51; FFU, 1.77; P < 0.0001), and physical function (PA, 31.34; FFU, 12.17; P < 0.0001). There were 6 reaspirations for recurrence (12.7%), and 1 patient underwent unicompartmental knee arthroplasty. There were no infections or other complications. Conclusion: Significant clinical improvement in patients with symptomatic popliteal cysts can be achieved via UGAFI as the sole treatment. Clinical Relevance: UGAFI is a safe and effective option as the sole treatment modality for symptomatic popliteal cysts.